The edge of belonging [large type] - Cox, Amanda, 1984- (Thorndike Press, A art of Gale, a Cengage Company, 2021)
When Ivy Rose returns to her hometown to oversee an estate sale, she discovers that her grandmother left behind more than trinkets and photo frames - she provided a path to the truth behind Ivy's adoption. Shocked, Ivy seeks clues to her past, but a key piece to the mystery is missing. Twenty-four years earlier, Harvey James finds an abandoned newborn who gives him a sense of human connection for the first time in his life. His desire to care for the baby runs up against the stark fact that he is homeless. When he becomes entwined with two people seeking to help him find his way, Harvey knows he must keep the baby a secret or risk losing the only person he's ever loved. - back cover